Formal coding and its relationship to aesthetic taste among students of the Department of Art Education (Al-Academy, 2023)
The current research aims to identify pictorial coding and its relationship to the aesthetic taste of art education students. The research community consisted of (10) plastic artworks, and (3) artworks were selected as a sample for analysis and decoding. With the aim of the research, the research tool was prepared as it consisted of an analysis form, and the researcher used statistical methods: Equation (Cooper) to find the percentage of agreement between the arbitrators and the equation (Scott) to calculate the validity of the tool, and the correlation coefficient (Pearson) to extract stability in the method of segmentation half. Shape formations and achieve encryption of the plastic image through decoding symbols, meanings, and the significance of shape, color, and artistic techniques. As for the most important conclusions: The pictorial coding led to the success of organizing the elements in a manner of high aesthetic value that prompts the recipient to communicate between the vocabulary of the plastic image and dive into the structure of the subject. Keywords- Formal coding- Aesthetic taste